Pulmonary Hemorrhage Secondary to Disseminated Strongyloidiasis in a Patient with Systemic Lupus Erythematosus - Erika P. Plata-Menchaca; V. M. De la Puente-Diaz de Leon; Adriana G. Peña-Romero; Eduardo Rivero-Sigarroa (Case Reports in Critical Care)
Introduction. Pulmonary hemorrhage secondary to disseminated strongyloidiasis is an unusual, well-recognized entity in immunocompromised patients with autoimmune disease, which is associated with the hyperinfection syndrome, sepsis, and a high mortality rate. Case Presentation. We present a case of a 44-year-old Mexican woman with systemic lupus erythematosus and acute bacterial meningitis who developed pulmonary hemorrhage with acute respiratory failure requiring mechanical ventilation, treated with broad spectrum systemic antibiotics and high dose methylprednisolone, who subsequently developed a characteristic purpuric skin eruption and septic shock and died two days later of refractory hypoxemia caused by massive pulmonary bleeding. The postmortem examination reports filariform larvae of S. stercolaris in lung, skin, and other organs. Conclusion. This case highlights the importance of considering disseminated strongyloidiasis in the differential diagnosis of diffuse alveolar hemorrhage in systemic lupus erythematosus, and screening for S. stercolaris infection before initiation of immunosuppressive therapy should be considered, especially in endemic areas. Disseminated strongyloidiasis has a high mortality rate, explained in part by absence of clinical suspicion.